Imagine-self perspective-taking and rational self-interested behavior in a simple experimental normal-form game - Adam Karbowski; Michał Ramsza (Frontiers in Psychology, 2017)
The purpose of this study is to explore the link between imagine-self perspective-taking and rational self-interested behavior in experimental normal-form games. Drawing on the concept of sympathy developed by Adam Smith and further literature on perspective taking in games, we hypothesize that introduction of imagine-self perspective-taking by decision-makers promotes rational self-interested behavior in a simple experimental normal-form game. In our study, we examined behavior of 404 undergraduate students in the two-person game, in which the participant can suffer a monetary loss only if she plays her Nash equilibrium strategy and the opponent plays her dominated strategy. Results suggest that the threat of suffering monetary losses effectively discourages the participants from choosing Nash equilibrium strategy. In game theory terms, the participants may rationally take the possibility of playing dominated strategy by their opponents into account, because the dominated strategy can be played due to not full rationality of the opponents or their specific not self-interested motivation. However, adopting imagine-self perspective by the participants promotes their rational self-interested behavior (indicated by Nash equilibrium choices), perhaps by alleviating their attributions of a susceptibility to errors or a non-self-interested motivation to the opponents. The imagine-self-self-interest link is next postulated and succinctly discussed in the context of relevant psychological and economic literature.
Keywords: D01; D00; 330; empathy; games